Scilla vardaria (Asparagaceae subfamily Scilloideae): a threatened new species of Scilla L. from Northeast Turkey with a floral corona - Yildirim, Hasan; Gemi̇ci̇, Yusuf; Wilkin, Paul (Phytotaxa, 2013)
Scilla vardaria Yıldırım & Gemici (Asparagaceae) is described as a new species. Diagnostic morphological characters, a full description and detailed illustrations are provided on the basis of the type specimen and observations of wild populations. The new species is characterized by the conical floral corona structure formed by fusion of its filaments, with anthers arising almost at the floral corona apex. Its seeds are borne in pyriform capsules and are oblong, straw to pale yellow with a cucullate, pale creamy yellow elaiosome which is adherent to the testa and the bulb is brown-pink. It is easily distinguished from all other Scilla species on the basis of these morphological characters.